The Role of Islamic Religious Education Teachers in the Globalization Era: Fostering the Morals of Modern Bani Adam Boyolali Madrasah Ibtidaiyah Students - Rini Kartika Sari; Meti Fatimah (Didaktika: Jurnal Kependidikan, 2024)
The aim of this research is to find out in depth the role of PAI teachers in the era of globalization in developing student morals. This research uses a qualitative approach. This research was conducted at MI Modern Bani Adam Boyolali in December 2023 with the informants in this research being the school principal, PAI teachers, student affairs officers and students. The data in this research was obtained through observation, structured interviews and documentation as well as relevant literature results. Data analysis uses the Miles and Huberman analysis model called interactive analysis. This analysis is divided into several stages: data collection, data reduction, data presentation, and drawing conclusions. The results show that at MIN Bani Adam Boyolali PAI teachers act as educators, motivators and facilitators in developing students' morals in the era of globalization. Then the strategy used by PAI teachers is habituation and an example.